On the interplay between turbulent forces and neoclassical particle losses in zonal flow dynamics. (13th September 2019) - Gerrú, R.; Mulas, S.; Losada, U.; Castejón, F.; Liu, B.; Estrada, T.; van Milligen, B.Ph.; Hidalgo, C.
Abstract: This study presents an investigation into the connection between radial electric fields, Reynolds stress gradients and long range correlations (LRCs), with the latter being a proxy for zonal flows (ZFs), in different plasma scenarios in the TJ-II stellarator. Monte Carlo simulations showed that radial electric fields with a similar size to those experimentally measured affect neoclassical orbit losses. Although the order of magnitude of turbulent acceleration was comparable to the neoclassical damping of perpendicular flows, we found that the dependence of this acceleration on the radial electric field did not correlate with the evolution of the LRC amplitude, indicating that turbulent acceleration alone cannot explain the dynamics of ZFs. These results are in line with the expectation that the interplay between turbulent and neoclassical mechanisms is an important ingredient of the dynamics of edge ZF.